Comunicação e Trabalho: binômio teórico produtivo para as pesquisas de recepção - Figaro , Roseli (Mediaciones Sociales, 2009)
This article presents theoretical and methodological basic ideas of an ergology approach on the communication area. To fulfill this objective, it highlights the human activity as being intrinsic to the communication and work concepts, composing, this way, the binomial communication and work. It emphasizes how, in the reception research, such approach proves productive and how it is being applied in work communication research.